2017
DOI: 10.3892/ol.2017.6140
|View full text |Cite
|
Sign up to set email alerts
|

Distinct DNA methylation alterations are associated with cribriform architecture and intraductal carcinoma in Gleason pattern 4 prostate tumors

Abstract: Abstract. The aim of the present study was to explore DNA methylation aberrations in association with cribriform architecture and intraductal carcinoma (IDC) of the prostate, as there is robust evidence that these morphological features are associated with aggressive disease and have significant clinical implications. Herein, the associations of a panel of seven known prognostic DNA methylation biomarkers with cribriform and IDC features were examined in a series of 91 Gleason pattern (GP) 4 tumors derived fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…This implies the presence of occult metastases at the time of treatment, which are not accurately predicted using standard clinical prognostic factors. We and others have used multi-omic approaches to identify candidate biomarkers that predict BCR 7 – 10 , 51 53 . While BCR is an early and easily measured endpoint, it is a weak surrogate of prostate cancer-specific mortality 5 , 6 .…”
Section: Discussionmentioning
confidence: 99%
“…This implies the presence of occult metastases at the time of treatment, which are not accurately predicted using standard clinical prognostic factors. We and others have used multi-omic approaches to identify candidate biomarkers that predict BCR 7 – 10 , 51 53 . While BCR is an early and easily measured endpoint, it is a weak surrogate of prostate cancer-specific mortality 5 , 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Olkhov-Mitsel et al [109] investigated the methylation profile of ALU, APC, CYP26A1, HOXD3, HOXD8, RASSF1, TBX15, TGF-β in IDC-P/CC lesions from 91 Gleason score 7 PCas and found an increase in the methylation levels of APC, RASSF15 and TBX15 in IDC-P/CC.…”
Section: Cases With Idc-p Compared To Cases Without Idc-pmentioning
confidence: 99%
“…Biologically, MED12 serves as an important regulator of the Wnt pathway, encompassing both canonical Wnt signaling and Wnt/PCP signaling 89 . A study demonstrated increased methylation levels of the APC gene in IDC‐P lesions, which further contributes to the activation of the Wnt pathway 21 . Furthermore, In a study focusing on BRCA2 ‐mutant prostate cancers, it was observed that tumors with IDC‐P exhibited a higher prevalence of genomic and epigenomic dysregulation of MED12 11 .…”
Section: Med12mentioning
confidence: 99%